Nonfatal agriculture injuries in children - A retrospective study - Huda, Farhanul; Wasim, Sanober (Indian Journal of Child Health, 2016)
Introduction: A larger proportion of the population in the world is involved in agriculture. Agricultural injuries are a major cause of morbidity and mortality both in developed as well as developing countries. These injuries can occur in all age groups. Objective: Since India is a predominantly agricultural country, we undertook this study to find out the pattern of agricultural injuries in children. Materials and Methods: This is a retrospective hospital-based study. Children